Biosynthesis of Gold Nanoparticles using Amomum subulatum and Their Catalytic Properties - Baghel, Sonam; Khurana, Monika (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Recent studies reveal that gold nanoparticles possess unique and promising applications, such as targeted drug delivery, cancer therapy, and environmental uses like water purification and pollutant detection. Thus, developing AuNPs through simple, eco-friendly, and cost-effective methods is crucial compared to traditional chemical synthesis. In this study, we employed a one-step method to prepare gold nanoparticles using seed extract from black cardamom. The nanoparticles were synthesized by mixing the seed extract and gold(III) chloride trihydrate in an aqueous solution on a magnetic stirrer at room temperature, with the seed extract acting as both a reducing and capping agent. The resulting wine-red colloidal AuNPs were characterized by UV-visible spectroscopy, showing a surface plasmon resonance band at 530.5 nm, indicating successful formation and stability of the nanoparticles over 2 months. the AuNPs had sizes ranging from 20 to 60 nm as revealed by transmission electron microscopy (TEM) and dynamic light scattering (DLS) studies and were predominantly spherical in shape with few being triangular. Fourier transform infrared spectroscopy (FTIR) detected the presence of functional groups on the biosynthesized AuNPs before and after reduction. A time-dependent comparative analysis of their catalytic activity demonstrated their effectiveness in degrading 4-nitro phenol and organic dyes like methylene blue, and methyl orange, achieving a degradation efficiency of 91%. Kinetic studies indicated that the reaction followed pseudo first-order kinetics. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).